Are Marxism and Democracy Antithetical? Two Opinions - Sehgal, M. L. (Advances in Social Sciences Research Journal, 2020)
No doubt, Marx believed that a representative government always overweighed an absolutist regime but he has his own views on democracy. He would neither appreciate the ‘direct’ nor the ‘parliamentary’ democratic forms because he was against the ‘universal franchise’; antithetical to today’s definition of the democracy. He started with Bourgeoisie Democracy’ of France but found it lacking because it was democratic according to CAPITALIST terms and was ‘democracy of the minority’. He was fascinated by ‘Commune Model of Democracy’ which was not a democracy in the true sense as it could neither be applied to the whole of length and breadth of the country nor the Commune was a parliamentary body, rather executive and legislative at the same time. In fact, Marx was too obsessed with ‘Capitalism’ viz.-a-viz the poor plight of the ‘Labour Class’ and always believed that any form of the government that did not emancipate the poor both politically and economically did not worth it.